1996
DOI: 10.1097/00043764-199608000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of Exposure to Benomyl in Nursery Workers

Abstract: We compared urinary levels of the metabolite methyl-5-hydroxy-2-benzimidazole carbamate (5-HBC) among nursery workers exposed to the fungicide benomyl (specifically Benlate 50 DF [DuPont, Wilmington, DE]) and workers not exposed to benomyl. Environmental exposures were quantitated from gloves, body patches, and air samples collected with area and personal monitors. The median concentration of 5-HBC in the urine of benomyl-exposed workers was 23.8 mumol of 5-HBC per mole of creatinine. No 5-HBC was detected in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…Hoekstra et a1 (18) found that, compared with re-entry activities, spraying doubled the exposure per workhour. In this study the mean spraying time per week among sprayers was 5.5 (SD 8.0, median 2) hours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hoekstra et a1 (18) found that, compared with re-entry activities, spraying doubled the exposure per workhour. In this study the mean spraying time per week among sprayers was 5.5 (SD 8.0, median 2) hours.…”
Section: Discussionmentioning
confidence: 99%
“…As dermal exposure is by far the most important (13,14,18), it seems reasonable to assume that the number of hours in contact with plants reflects the level of exposure. At least 20 hours per week was chosen as an indicator of at least half-time dermal contact to cultures.…”
Section: Discussionmentioning
confidence: 99%
“…Indirectly, researchers have examined various ways to assess the amount of 1-naphthol attributable to carbaryl exposure; however, this remains an inexact measurement of carbaryl exposure. 125,126 Other carbamate metabolites that have been measured in urine include benomyl, 127 …”
Section: Op Insecticidesmentioning
confidence: 99%
“…For example, in both industries most of the work is performed in enclosed environments, where pesticides cannot dissipate as easily as in open fields [28]. Exposure to pesticides can be dermal, oral, and respiratory and can occur through direct contact with pesticides during application, contact with pesticide residue on plants, upon entering a recently treated area, or through drift from nearby applications [29].…”
Section: Introductionmentioning
confidence: 99%